Ergonomic Analysis of Working Positions in Petis Processing with the RULA Method at UD Murni Sidoarjo - Immannulloh, Dimas; Tranggono, Tranggono (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
UD Murni Sidoarjo is a company that focus on making petis as traditional food of Sidoarjo. But, often they experience ergonomic problems which results in Work Related Musculoskeletal Disorders (WRMSDs) for their workers. The method that used in this study, namely Rapid Upper Limb Assesment (RULA) which is a method for  assessing posture, style, and movement of an activity related to upper limb users. The main objective in this study is to analyze the working postures of filters sector from petis processing industry by using Rapid Upper Limb Assesment (RULA) in CATIA V5R21 software. 5 out of 5 workers postures from filters sector indicated a high risk score of 6, indicating changes in the posture is needed to be done. Tool design with ergonomic interventions are suggested and the improved posture was evaluated using Conventional RULA Asessment and CATIA V5R21 software. From 2 asessment, the posture indicated a score of 3, indicating low risk. The results from this study indicate that awkward working posture risks can be minimized effectively using ergonomic interventions with design of working tools in solidworks software that being analyzed with CATIA V5R21 software. The limitation of this study is the tool that had been design is not used by real workers, the design of the tool is only emplimented into CATIA V5R21 software which is used for RULA asessment, the design can be realized by any future researcher for another impact not just posture but also production, performance, and the others.